Iguratimod improves bleomycin-induced pulmonary inflammation and fibrosis by regulating macrophage polarization through inhibiting the TLR4/NF-κB pathway - Xu, Huan; Ma, Kaixuan; Ma, Ziting; Zhuang, Tianyu; Lin, Ling (Frontiers in Immunology, 2025)
IntroductionPulmonary fibrosis (PF) is a fatal pathological subtype of interstitial lung disease, frequently manifests as a pulmonary complication of connective tissue disease. Iguratimod (IGU) is a new class of anti-rheumatic drugs used in the treatment of rheumatoid arthritis (RA). Studies have reported that RA patients treated with IGU have better lung function, and IGU effectively ameliorates PF. However, the mechanism by which IGU improves PF is still unclear. This study aims to elucidate the therapeutic efficacy and mechanisms of IGU in PF through in vivo and in vitro investigations, so as to provide a new treatment method for PF.MethodsIn our research, bleomycin (BLM)-induced PF of mice were used to observe the therapeutic effect of different concentrations of IGU. And the effects of IGU on macrophage polarization and activation pathway TLR4/NF-κB in lung tissue were analyzed. In addition, Raw264.7 macrophages were induced to M1 and M2 polarization in vitro, and the effects of IGU on Raw264.7 macrophage polarization and related pathways were observed.ResultsIn our study, database analysis suggested that macrophage polarization-relative genes and pathways as well as TLR4 activation played important roles in BLM-induced PF in mice. Besides, we found that IGU effectively ameliorated BLM-induced PF and epithelial-mesenchymal transition in mice, and inhibited the polarization of M1/M2 macrophages at different stages of PF. Moreover, In vitro studies further demonstrated that IGU suppressed M1 polarization of Raw264.7 and its activation pathway TLR4/NF-κB.DiscussionIn summary, IGU inhibits the activation of macrophages and M1 polarization through inhibiting the TLR4/NF-κB pathway, thereby improving BLM-induced pulmonary inflammation and fibrosis in mice. It is suggested that IGU may be a new therapeutic option for interstitial pulmonary fibrosis.